2012
DOI: 10.1021/jm301144g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and SAR of b-Annulated 1,4-Dihydropyridines Define Cardiomyogenic Compounds as Novel Inhibitors of TGFβ Signaling

Abstract: A medium-throughput murine embryonic stem cell (mESC)-based high-content screening of 17,000 small molecules for cardiogenesis led to the identification of a b-annulated 1,4-dihydropyridine (1,4-DHP) that inhibited Transforming Growth Factor β (TGFβ)/Smad signaling by clearing the type II TGFβ receptor from the cell surface. Since this is an unprecedented mechanism of action, we explored the series' structure activity relationship (SAR) based on TGFβ inhibition, and evaluated SAR aspects for cell-surface clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 31 publications
2
63
0
1
Order By: Relevance
“…(7,8) Interestingly, these mechanistic studies also revealed that the stereoselective mode of action was reversed for calcium channel antagonism since only the (-)-enantiomers strongly inhibited calcium transients in rat cardiomyocytes whereas the TGFβ inhibiting (+)-enantiomers were weakly active. (8) One of the designated goals of our ongoing work is to define a detailed picture of the …”
Section: X-ray Crystal Structure Analysismentioning
confidence: 96%
See 3 more Smart Citations
“…(7,8) Interestingly, these mechanistic studies also revealed that the stereoselective mode of action was reversed for calcium channel antagonism since only the (-)-enantiomers strongly inhibited calcium transients in rat cardiomyocytes whereas the TGFβ inhibiting (+)-enantiomers were weakly active. (8) One of the designated goals of our ongoing work is to define a detailed picture of the …”
Section: X-ray Crystal Structure Analysismentioning
confidence: 96%
“…Therefore, the newly synthesized compounds were designed to incorporate heteroatom-containing, polar functional groups but also to explore steric aspects of certain regions of the molecules. Compounds were evaluated in a TGFβ/Smad reporter gene assay in HEK293T as described before, (8) and the data is summarized in Table 1. (20a and 21a), a carboxylic acid group pointed out the limitation of introducing a negatively charged moiety in the 2-position since both compounds were inactive.…”
Section: Tgfβ β β β/Smad Inhibitionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent study shows that degradation of the TGF-β type II receptor (TGFBR2) by ITD-1, a novel molecule that is a highly selective TGF-β pathway inhibitor, leads to differentiation of mouse ESC into cardiomyocytes suggesting a role of inhibition of TGF-β signaling in heart development and potential role in regeneration [39,40]. The effects on differentiation were dependent on timing of treatment: when the inhibitor was added at days 3-5 of differentiation, it resulted in formation of cardiac cells; in contrast treatment during days 1-3 of differentiation abolished this effect.…”
Section: Tgf-β Inhibitorsmentioning
confidence: 99%